THE ROLE OF E-TRUST AND BRAND IMAGE ON REPURCHASE INTENTION SHOPEE FOOD - Afridhianika, Annisa Nugraheni; Harisudin, Mohamad; Handayani, Sugiharti Mulya (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The objective of this study is to examine the impact of E-trust and brand image on the association between E-Service Quality and sales promotion about Shopee Food consumer repurchase intention. The research methodology used is quantitative, with the sampling technique being convenience sampling. A total of 105 students from universities in Surakarta were selected as the research subjects. Research analysis employs PLS-Structural Equation Modeling (SEM). The findings of this study indicate that E-Service Quality, sales promotion, brand image, and E-Trust have a favourable and statistically significant impact on repurchase intention. The association between E-Service Quality and sales promotion and Shopee Food consumer repurchase intention is influenced by Brand image and E-Trust. The findings of this study can inform marketing strategies for marketplace platforms by optimizing E-Service Quality, sales promotion, Brand Image, and trust. These characteristics have been empirically shown to enhance consumer repurchase intention.